Egg quality and production by the addition of dried consortium probiotics on late-phase laying hens - Nabila, Tissiana Irca; Adriani, Lovita; Latipudin, Diding; Mushawwir, Andi; Mayasari, Novi (Universitas Sebelas Maret, 2023)
Objective: Lactic acid bacteria are known to improve performance and gut health of laying hens. Several potential microbiotas that could enhance gut health are Lactobacillus acidophilus, Lactobacillus bulgaricus, Streptococcus thermophilus, and Bifidobacterium sp. Probiotics are microorganisms that play a role in improving the ecosystem of intestinal flora, which affects nutrient absorption process along with metabolism, and increase the production of eggs. This study aimed to determine the effect of the microbiota consortium in probiotic powder on egg quality and production for late-phase laying hens.Methods: This research was done on January-April 2022 and used 40 Lohmann brown laying hens aged 70 weeks. The treatments given were 0, 2, 3, and 4% probiotic powder in laying hens’ feed. Egg samples were collected every week, and parameters observed in the study were egg quality consisting egg weight, egg volume, and egg weight composition such as yolk weight, egg white weight, eggshell weight, yolk index, haugh unit, and egg production.Results: The result of the study showed that the addition of probiotic powder could not enhance the egg quality (P>0.05) based on egg weight, volume, yolk index, haugh unit, and egg weight composition. However, a 4% level of probiotic powder could improve egg production significantly (P<0.01).Conclusions: Hence, we can conclude that probiotic powder could be used as a feed additive to improve egg production in late-phase laying hens.